Kewajiban Perusahaan Perkebunan Kelapa Sawit Dalam Memfasilitasi Kebun Plasma: (Studi Kasus di Kota Lama, Kabupaten Rokan Hulu, Riau) - Mahrus, Abdul Kamil Abdurrahman (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2025)
This research analyzes the obligation of palm oil plantation companies to facilitate the development of plasma plantations, especially after the enactment of the Job Creation Law. The policy of developing plasma plantations in Indonesia has experienced quite complex dynamics, with various regulations that complement each other but also create uncertainty. An analysis of various laws and regulations shows an inharmony regarding the calculation of the land area that must be allocated for plasma plantations. Therefore, this study concludes that it is necessary to revise the existing laws and regulations to provide legal certainty and reduce the potential for conflict.